Metode Pembelajaran Suling Laras Slendro Gaya Yogyakarta - Marsudi, Marsudi Marsudi (Resital: Jurnal Seni Pertunjukan, 2022)
This research is motivated by the fact that many flute players, artists, musical practitioners and students do not recognize the characteristics of the Yogyakarta style flute, so there is a tendency to abandon it. On the other hand, the Yogyakarta style flute instrument has specifications that lead to special characteristics. This study aims to provide an understanding of the Yogyakarta style flute as well as produce teaching materials for the Yogyakarta style flute as a guide for learning. This study uses two methods, namely data collection and analysis and design methods. Yogyakarta Style flute learning techniques include: knowledge of the flute, basic techniques, intermediate techniques, and advanced techniques. Knowledge of the flute includes the characteristics of the shape, blow hole, tone hole, closing tone, cengkok seleh, and the application of cengkok seleh flute Yogyakarta style. Basic techniques include mastery of blowing and closing types in finding the tone of both the slendro  barrels. Intermediate techniques include basic mastery of crooked selh, slendro barrel and pelog barrel. Advanced techniques include the application of seleh bends on the gending and lagon.